2008
DOI: 10.1021/jp8051642
|View full text |Cite
|
Sign up to set email alerts
|

The Binding Behavior of Cyclodextrins toward a Nitroxide Spin Probe in the Presence of Different Alcohols As Studied by EPR

Abstract: Stability constants, rates of association and dissociation, and thermodynamic and activation parameters for the formation of inclusion complexes between the radical guest, N-benzyl- tert-butyl- d 9-nitroxide and beta- or 2,6- O-dimethyl-beta-cyclodextrin (CDs), have been determined by EPR spectroscopy in water in the presence of 14 different alcohols, differing in size and lipophilicity. In all cases, it was found that addition of alcohol, depending on its structure and concentration, causes a reduction of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The same authors detected “multimodal” inclusion: in the case of a nitroxide with several functional groups, different complexes were generated, depending on the group that became the guest . The choice of an interesting nitroxide led to the detection, with excellent resolution due to d -enrichment, of different ESR spectra for the “in” and “out” nitroxides (inside and outside the CD host), with assignment based on the a N values . More recently, it was demonstrated that pulse ESR methods such as electron spin−echo envelope modulation (ESEEM) and double electron−electron resonance (DEER) can lead to additional structural information compared to continuous wave (CW) ESR …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The same authors detected “multimodal” inclusion: in the case of a nitroxide with several functional groups, different complexes were generated, depending on the group that became the guest . The choice of an interesting nitroxide led to the detection, with excellent resolution due to d -enrichment, of different ESR spectra for the “in” and “out” nitroxides (inside and outside the CD host), with assignment based on the a N values . More recently, it was demonstrated that pulse ESR methods such as electron spin−echo envelope modulation (ESEEM) and double electron−electron resonance (DEER) can lead to additional structural information compared to continuous wave (CW) ESR …”
Section: Introductionmentioning
confidence: 99%
“…7 The choice of an interesting nitroxide led to the detection, with excellent resolution due to D-enrichment, of different ESR spectra for the "in" and "out" nitroxides (inside and outside the CD host), with assignment based on the a N values. 8 More recently, it was demonstrated that pulse ESR methods such as electron spin-echo envelope modulation (ESEEM) and double electron-electron resonance (DEER) can lead to additional structural information compared to continuous wave (CW) ESR. 9 NMR studies have added important details on the relative location of guests in R-, β-, and γ-CDs.…”
Section: Introductionmentioning
confidence: 99%
“…As a first example, the EPR method was employed for studying the effect of aliphatic alcohols on the kinetic of complexation by CDs . In this work we also found that substitution of the tert ‐butyl hydrogens of BTBN1 by deuterium atoms significantly improve the spectral resolution of EPR lines and, thus, the accuracy in measuring the kinetic rate constants.…”
Section: Host–guest Systemsmentioning
confidence: 67%
“…Stability constants of complexes between CD and the various alcohols were determined. 102 The ternary inclusion complexes of two spin-labeled pyrrolidineand piperidine-containing indole derivatives and two hydrocarbons, benzene and cyclohexane, with gand b-cyclodextrins (CD) (altogether eight complexes) were prepared and studied by ESR in the solid phase over a broad temperature range. For most ternary complexes, the hydrophobicity of the NO group environment is much higher than for binary complexes devoid of hydrocarbons.…”
Section: Organic Radicalsmentioning
confidence: 99%